Comparing NICU teamwork and safety climate across two commonly used survey instruments. Issue 12 (23rd December 2015) - Profit, Jochen; Lee, Henry C; Sharek, Paul J; Kan, Peggy; Nisbet, Courtney C; Thomas, Eric J; Etchegaray, Jason M; Sexton, Bryan
Abstract : Background and objectives: Measurement and our understanding of safety culture are still evolving. The objectives of this study were to assess variation in safety and teamwork climate and in the neonatal intensive care unit (NICU) setting, and compare measurement of safety culture scales using two different instruments (Safety Attitudes Questionnaire (SAQ) and Hospital Survey on Patient Safety Culture (HSOPSC)). Methods: Cross-sectional survey study of a voluntary sample of 2073 (response rate 62.9%) health professionals in 44 NICUs. To compare survey instruments, we used Spearman's rank correlation coefficients. We also compared similar scales and items across the instruments using t tests and changes in quartile-level performance. Results: We found significant variation across NICUs in safety and teamwork climate scales of SAQ and HSOPSC (p<0.001). Safety scales (safety climate and overall perception of safety) and teamwork scales (teamwork climate and teamwork within units) of the two instruments correlated strongly (safety r=0.72, p<0.001; teamwork r=0.67, p<0.001). However, the means and per cent agreements for all scale scores and even seemingly similar item scores were significantly different. In addition, comparisons of scale score quartiles between the two instruments revealed that half of the NICUs fell into different quartiles when translating between the instruments. Conclusions: Large variation and opportunities for improvement in patient safety culture exist across NICUs. Important systematic differences exist between SAQ and HSOPSC such that these instruments should not be used interchangeably.